"Give me perfection or nothing!": The impact of perfectionism on product evaluation as moderated by secrecy effect and name volatility. Issue 6 (22nd July 2021) - Ker, Wen‐Ying; Kao, Danny Tengti
Abstract: While perfectionism has been extensively explored in psychiatric and clinical psychology literature, theoretical understanding of the effects of perfectionism on consumers' evaluations of the advocated product is promising but underexplored. Therefore, this research aims to employ cases of perfectionism and secrecy effect to examine whether name volatility can moderate consumers' product evaluations. The experiment was designed to examine the effect of perfectionism on product evaluation by presenting a variety of advertisements that differed in name volatility and secrecy context manipulation. In the experiment, a total of 217 participants were randomly assigned to a 2 (secrecy context: secret vs. non‐secret) × 2 (name volatility: volatile vs. calm) × 2 (perfectionism: self‐oriented vs. socially prescribed) between‐subjects factorial design. Results demonstrated that for consumers who showed variances in the type of perfectionism, advertisements characterized by different secrecy (secret context vs. non‐secret context) and name volatility (volatile vs. calm) will lead to differential product evaluations. This research takes up the call to extend the limited attention given to perfectionism in the domain of marketing. Specifically, this research aims to explore how consumers' perfectionism affects their product evaluations and the moderating effects of secrecy and name volatility.